The experiences of women with polycystic ovary syndrome on a very low-calorie diet - Love JG; McKenzie JS; Nikokavoura EA; Broom J; Roll; C; Johnston KL (Dove Medical Press, 2016)
John G Love,1 John S McKenzie,2 Efsevia A Nikokavoura,3 John Broom,3 Catherine Rolland,3 Kelly L Johnston4,5 1School of Applied Social Studies, Faculty of Health & Social Care, Robert Gordon University, Aberdeen, UK; 2Rowett Institute of Health & Nutrition, University of Aberdeen, St Mary’s, Kings College, Aberdeen, UK; 3Centre for Obesity Research, Faculty of Health & Social Care, Robert Gordon University, Aberdeen, UK; 4LighterLife, Harlow, Essex, UK; 5Diabetes and Nutritional Sciences Division, Faculty of Health and Medical Sciences, Kings College London, London, UK Abstract: Polycystic ovary syndrome (PCOS) is variously reported to affect between 5% and 26% of reproductive age women in the UK and accounts for up to 75% of women attending fertility clinics due to anovulation. The first-line treatment option for overweight/obese women with PCOS is diet and lifestyle interventions. However, optimal dietary guidelines are missing, with very little research having been done in this area. This paper presents the findings from a qualitative study (using semistructured interviews) of ten obese women who had PCOS and who had used LighterLife Total (LLT), a commercial weight loss program which utilizes a very low-calorie diet in conjunction with behavioral change therapy underpinned by group support. We investigated the women’s history of obesity, their experiences of other diets compared with LLT, and the on-going impact that this has had on their lives. Findings show that most women reported greater success using this weight loss program in terms of achieving and maintaining weight loss when compared with other diets. Furthermore, all the women nominated LLT as their model weight loss intervention with only a few modifications. Keywords: PCOS, obesity, weight loss, diet